Placing the Public in Public Health in Post-War Britain, 1948–2012 - Mold, Alex; Clark, Peder; Millward, Gareth; Payling, Daisy (Medicine and Biomedical Sciences in Modern History, 2019)
VIII, 141 p. 1 illus. in color.